Multifunctional applications of algae in environmental sustainability, food, agriculture, and biotechnology: current advances and future perspectives - Mohammad Khalil R Monjed (World Journal of Biology Pharmacy and Health Sciences, 2026)
Algae represent a diverse and versatile group of photosynthetic organisms with considerable potential for addressing environmental, agricultural, nutritional, and industrial challenges. This review provides an overview of recent advances in algal biotechnology, with particular emphasis on the multifunctional applications of microalgae, macroalgae, and cyanobacteria in environmental sustainability, food and nutrition, agriculture, and health. In environmental applications, algae can serve as bioindicators of pollution and contribute to the removal of heavy metals, nutrients, and organic contaminants from wastewater and other contaminated environments. Their roles in nitrogen fixation, soil improvement, carbon sequestration, and the development of sustainable agricultural practices are also discussed. From a nutritional perspective, algae provide proteins, essential amino acids, polyunsaturated fatty acids, vitamins, minerals, dietary fiber, polysaccharides, and other bioactive compounds, supporting their incorporation into functional foods, fermented products, meat and dairy formulations, and cereal-based foods. Algal-derived compounds, including carotenoids, phycobiliproteins, polyphenols, polysaccharides, sterols, and bioactive peptides, have demonstrated antioxidant, anti-inflammatory, antimicrobial, antidiabetic, and potential anticancer activities, although further clinical evidence is required to establish their therapeutic efficacy. The review also considers the potential of algae as sustainable sources of protein, biofuels, bioplastics, and other value-added bioproducts. Despite these advantages, challenges related to cultivation costs, harvesting, biomass processing, environmental variability, food safety, scalability, regulatory requirements, and economic feasibility continue to limit widespread commercialization. Future advances in strain improvement, integrated cultivation systems, algal–microbial interactions, resource recovery, and algal biorefineries may help overcome these limitations. Overall, algae represent promising biological platforms for developing circular and sustainable solutions across food production, agriculture, environmental management, and biotechnology.